2020
DOI: 10.1101/2020.02.19.956854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social isolation modulates appetite and defensive behavior via a common oxytocinergic circuit in larval zebrafish

Abstract: 24How brains encode social stimuli and transform these representations into advantageous 25 behavioral responses is not well-understood. Here, we show that social isolation activates an 26 oxytocinergic, nociceptive circuit in the larval zebrafish hypothalamus. We further demonstrate 27 that chemical cues released from conspecific animals modulate its activity to regulate defensive 28 behaviors and appetite. Our collective data reveals a model through which social stimuli can be 29 integrated into fundamental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…The social responses observed in group swimming experiments and the responses we probed using the VR assay were based solely on visual input. Previous studies showed that larval zebrafish also use non-visual cues, such as mechanosensory (33, 56) and chemical stimuli (32) for social interactions. In this study we did not test how different sensory modalities operate jointly to support collective behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The social responses observed in group swimming experiments and the responses we probed using the VR assay were based solely on visual input. Previous studies showed that larval zebrafish also use non-visual cues, such as mechanosensory (33, 56) and chemical stimuli (32) for social interactions. In this study we did not test how different sensory modalities operate jointly to support collective behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we did not test how different sensory modalities operate jointly to support collective behavior. It will be interesting to test how visual information at longer distances is supported by mechanosensory sensation at shorter distances to elicit social responses (33), or how visual social information is related to chemical stimulation that represents conspecifics (32). These combinations can now be tested in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although fish have many sensory inputs that contribute to group behaviors, zebrafish are highly visual 28,30,35 , suggesting that visual drives likely play a dominant role. Other sensory modalities, such as somatosensation through the lateral line 19,20 and olfaction 13,21 , undoubtedly also can play a role in modulating social interactions, as might currently less decipherable elements such as "internal state" [12][13][14] and "personality" [15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…To achieve such synchronized movements in groups, individual members need to assess certain properties of their near neighbors, including their speed, distance, and orientation, and they need to respond rapidly to these features and then execute the appropriate motor commands. The ability to perform such socially relevant sensorimotor transformations, and thereby the ability to form groups, differ between different genetic backgrounds [8][9][10][11] and are modified by hunger [12][13][14] and innate "personalities'' of individual fish 15,16,17,18 . Further, while inputs from several sensory modalities, such as lateral line mechanoreception 19,20 , olfaction 21,22 and vision, all likely play a role in this process, vision is critical to certain attributes, such as the rapidity of turning responses, the necessary integration of distal cues, and the precision of the alignment responses 11,23,24 .…”
Section: Introductionmentioning
confidence: 99%